Evaluating the Impact of Informal Institutional Arrangements on the Transfer of Development Rights for Built Heritage Conservation in Dense Cities. - Hou, Jun; Chan, Edwin H. W.; Yung, Esther H. K. (Taylor & Francis, 2021)
Transfer of development rights (TDRs) is an attractive method in theory, contributing to a city’s conservation effort while balancing the need for sustainable urban development. Operationally, the implementation of TDRs is complex and problematic due to conflicting interests of stakeholders under the influence of different institutional arrangements. This study aims to show from a theoretical perspective how TDR cases for built heritage conservation are evaluated to examine the impact of TDR institutional arrangements, and then propose strategies to improve the institutional system. Through a review of established theories, an evaluation framework with a set of criteria and associated sub-criteria related to the outcomes of institutional arrangements was established for detailed impact analysis, which has been supported with feedback from semi-structured interviews with experts and interested groups. The outcome includes conflicts associated with Ostrom’s (2005) evaluative criteria for economic efficiency problems, social inequity, inadaptability and non-resilience with existing planning systems, unclear accountability, and undesirable “conformance with general morality”. The results of this case study reveal the gaps between the theory and practice of TDR implementations, particularly the conflicts with government planning systems and threats to public interests. Based on the results of this study, strategies have been provided that improve institutional arrangement for TDRs and highlight the specific measures needed to minimise the bilateral challenge between private development interests and public conservation goals.
Keywords: Stadtplanung; Bebauungsplanung; Denkmalpflege; Bauhöhe; Interessenkonflikt; Städtebaurecht; Bebauungsrecht; Konfliktmanagement; Konfliktanalyse; Transfer of Development Rights (TDR)